Applied Informatics in SME Digital Transformation: Integrating Bai Salam Islamic Contracts with Odoo ERP System in the Garment Industry - Octaviano, Dicky (Universitas Mercu Buana, 2026)
In the era of digitalization, Small and Medium Enterprises (SMEs) in Indonesia face challenges in managing Sharia-compliant transactions efficiently. This study applies informatics principles to integrate Bai Salam contracts (prepaid forward sales in Islamic finance) into the open-source Odoo ERP system at a garment SME in Bekasi. Using a qualitative descriptive case study with mixed methods, we customized Odoo modules for transaction recording, inventory management, and real-time reporting to ensure Sharia compliance and operational transparency. Results show a 13% improvement in financial performance ratios (from 1.15 to 1.28) and reduced transaction errors by 85%, demonstrating the efficacy of applied informatics in enhancing SME efficiency. This framework provides practical guidelines for informatics-driven digital transformation in Sharia-based SMEs.